From Lessons Learned the Hard Way to Lessons Learned the Harder Way - Andria Foote Schwegler (Park University, 2013)
My departure from traditional methods of teaching and assessment (i.e., lecture and close-ended exams) was prompted years ago by a "gut feeling" that has morphed into an explicit examination of my teaching practice and students' reactions to it. The scholarly approach and empirical evidence in "Teachers and Learning" (Hutchings, Huber & Ciccone, 2011, Chapter 2) provided me with the scientific and social support I needed to publically challenge existing norms regarding teaching practices, reevaluate my data collection efforts, and advocate for change based on best practices, not on tradition, both inside my classroom and beyond.